Mechanistic Study of Rail Gouging during Hypersonic Rocket Sled Tests - Xuewen Zhou; Huadong Yan; Cheng Chen; Yuanfeng Yu (Advances in Materials Science and Engineering)
Gouging—an obstacle to the development of hypersonic rocket sled test techniques—was mechanistically investigated through experimental and theoretical analyses. Typical gouges were analyzed using macroscopic and microscopic experiments to investigate the evolution of gouging. Quasistatic compression and Hopkinson bar experiments were performed to systematically study the thermoviscoplastic properties of U71Mn rail steel under wide ranges of the strain rate and temperature. The critical condition for gouging was derived based on a thermoviscoplastic constitutive model supplemented by a three-variable criterion for an adiabatic shear instability. The results showed the following. (1) Adiabatic shear bands (ASBs) form when stress reduction under the combined action of frictional heating and high-speed deformation exceeds the strain-hardening effect of the rail material. (2) The nonuniform deformation of the edges of ASBs leads to the generation of cracks that split the rail surface. As the ASBs expand, the cracks grow and coalesce, eventually causing the material to peel off, forming gouges. (3) The relationships among the temperature, strain rate, and strain at the onset of gouging can be determined based on the critical condition for the formation of ASBs in rail steel.